“If only I were Isis”:: Remembrance, Ritual, and Writing in Lola Lemire Tostevin’s Cartouches - Gerry, Thomas (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2003)
Simultaneously a meditation on death and an enacted ritual towards renewal and consolation, the poems in Lola Lemire Tostevin's Cartouches are a tribute to the power of languages to provide a negotiation through grief and understanding, using the poet's Egyptian pilgrimage as the crucial point of journey and intuitive comprehension. Ruminating on the sacralization of death and renewal in another culture, Tostevin navigates grief and consolation through language and ritual. Hieroglyphs have "intuitive or emotional knowledge," and the Isis hieroglyph is invoked as part of the ritual of consolation, as a life-symbol rather than as a death-symbol. What evolves is a found site for interaction with the dead, and a renewal based on bodily inscription.